The Role of Education Policy in Indonesia in Improving the Professionalism of PAI Teachers in the Era of Society 5.0 - Munawir, Munawir; Qolby A., Nasywa Fairuzah; Pamenang, Frigit Aryo (YASIN, 2025)
The era of Society 5.0 necessitates that Islamic Education (PAI) teachers adapt to technological advancements to enhance their professionalism. This study investigates the influence of Indonesian education policies on the competence development of PAI teachers. Employing a literature review methodology, the research analyzes policies related to teacher professional development. The findings reveal that effective policies encompass technology-based training, digital certification, and Continuing Professional Development (CPD). Furthermore, the integration of Artificial Intelligence (AI) and big data in learning assessments significantly enhances teaching quality. The provision of digital infrastructure and incentives for exemplary teachers also plays a crucial role in elevating professionalism. Additionally, data-driven performance evaluations facilitate an objective measurement of policy effectiveness. Importantly, education policy strengthens teachers' autonomy and fosters educational innovation. Thus, it is imperative to implement adaptive and technology-focused education policies to equip PAI teachers with skills that meet contemporary demands.